2014
DOI: 10.1007/s40261-014-0236-8
|View full text |Cite
|
Sign up to set email alerts
|

A New Reversible and Potent P2Y12 Receptor Antagonist (ACT-246475): Tolerability, Pharmacokinetics, and Pharmacodynamics in a First-in-Man Trial

Abstract: Oral doses of ACT-281959 and ACT-246475 were well tolerated. Platelet inhibition correlated with ACT-246475 exposure. Exploratory formulations enhanced the bioavailability and antiplatelet effect of ACT-246475.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…Plasma concentrations of ACT‐246475 were determined using a validated liquid chromatography coupled to tandem mass spectrometry assay with a lower limit of quantification of 1 ng/mL . The method was linear in the concentration range 1‐2000 ng/mL.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Plasma concentrations of ACT‐246475 were determined using a validated liquid chromatography coupled to tandem mass spectrometry assay with a lower limit of quantification of 1 ng/mL . The method was linear in the concentration range 1‐2000 ng/mL.…”
Section: Methodsmentioning
confidence: 99%
“…ACT‐246475 is a potent, reversible, and selective nonthienopyridine antagonist of the P2Y 12 receptor that is being developed for subcutaneous (SC) self‐administration using an injector for the early treatment intervention of a suspected acute myocardial infarction . Preclinical studies using the ferric chloride model in rats showed that ACT‐246475 displays a wider therapeutic window with respect to bleeding risk than clopidogrel and ticagrelor .…”
mentioning
confidence: 99%
See 3 more Smart Citations